If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-5x+9=2-(x-3)
We move all terms to the left:
2x-5x+9-(2-(x-3))=0
We add all the numbers together, and all the variables
-3x-(2-(x-3))+9=0
We calculate terms in parentheses: -(2-(x-3)), so:We get rid of parentheses
2-(x-3)
determiningTheFunctionDomain -(x-3)+2
We get rid of parentheses
-x+3+2
We add all the numbers together, and all the variables
-1x+5
Back to the equation:
-(-1x+5)
-3x+1x-5+9=0
We add all the numbers together, and all the variables
-2x+4=0
We move all terms containing x to the left, all other terms to the right
-2x=-4
x=-4/-2
x=+2
| X+4x+x+4x=x+4x+39 | | 9-6y=3 | | 3+1.1=u | | u+14/7=3 | | 4∙3^x/5=36 | | 8x-20+2x-30=180 | | 3=-1/3(c) | | (y+150)^2=50 | | 4∙3x/5=36 | | f-7/9=4/9 | | 3x3-6=3 | | y=23+60 | | 75=5(b-80) | | 6x-20=4x-50 | | v-4.74=7.46 | | c-3/8=5/8 | | C=s+11 | | 1028-85x=1400 | | -2+8(n+6)=86 | | 17=w/6+10 | | 8y+12=y | | 22=6x-24 | | N+4n-2+5n-7=91 | | 2m-15=37 | | 2(5x+10)-2=28 | | 2.5/35=2/d | | 4.8-4=h | | -7x-8=-57 | | -7(4n+4)=-84 | | -14=3/7(3-9m) | | 2z-34=48 | | 2(-6m+7)=98 |